2020
DOI: 10.4111/icu.2020.61.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Single-port robot-assisted radical prostatectomy with the da Vinci SP system: A single surgeon's experience

Abstract: Purpose: To report an initial single-surgeon experience with single-port robot-assisted radical prostatectomy (SP-RARP) using the da Vinci SP surgical system (Intuitive Surgical, USA). Materials and Methods: Between December 2018 and October 2019, a single surgeon performed SP-RARP in 20 patients with prostate cancer. SP-RARP was performed using the conventional approach through an umbilical port with a GelPOINT access system (Applied Medical, USA) and an additional assist port. During surgery, the camera was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
1
9
1
Order By: Relevance
“…Notably, cases performed with the SP platform were associated with decreased median lymph node yields. Both values are lower than previously reported lymph node yields for both SP as well as RS-RALP with median values of 19 and 15 lymph nodes, respectively [ 7 , 24 ]. A potential reason for this is that our group detected high rates of symptomatic lymphoceles early on in our experience with RS-RALP [ 15 ].…”
Section: Discussioncontrasting
confidence: 68%
“…Notably, cases performed with the SP platform were associated with decreased median lymph node yields. Both values are lower than previously reported lymph node yields for both SP as well as RS-RALP with median values of 19 and 15 lymph nodes, respectively [ 7 , 24 ]. A potential reason for this is that our group detected high rates of symptomatic lymphoceles early on in our experience with RS-RALP [ 15 ].…”
Section: Discussioncontrasting
confidence: 68%
“…of days : 1 = 37 (94.9%) 2 = 2 (5.1%) Clavien ≥ 2 = 2 (5.1%) Kim et al . (2020) [ 14 ] 20 245 (200–255) 200 (150–300) 0 (0%) 11 (55%) 0 (0%) 0 (0%) 7 days (4–8) Clavien ≥ 2 = 0 (0%) Jones et al . (2020) [ 13 ] 23 236 (191–343) 50 (20–500) 0 (0%) 12 (52.2%) 0 (0%) 1 (4.3%) 1 day (range, 1–6) Clavien ≥ 2 = 6 (26.1%) Abaza et al .…”
Section: Resultsmentioning
confidence: 99%
“…The latest research results show that there is no significant difference in perioperative and pathological results between single-incision RARP and standard laparoscopic multiple-incision RARP. Some studies have reported that single-incision surgery may have more advantages in the recovery of postoperative erectile function [12][13][14] , but there are also reports that single-incision surgery takes a longer time because of the establishment of space 15,16 . This is because although the robot system multijoint instrument arm and simulated wrist instrument improve the problem of too narrow operation space to some extent, the collision between robotic arms will still occur during placement of a slightly large free suture, which also makes it more difficult for assistants to cooperate.…”
Section: Discussionmentioning
confidence: 99%